Interception loss simple model / Azinoor Azida Abu Bakar and Muhammad Khairudin Khalil - Abu Bakar, Azinoor Azida; Khaiil, Muhammad Khairudin (Division of Research and Industry Linkages, 2017)
Canopy interception is the phenomena where the water does not reach the ground. In this study, a model was developed to calculate the amount of interception loss from forest canopy. Two sources of interception were considered in order to develop the model. The physical interception was determined by the function of annual interception obtained from interception with high resolution. The calculated interception with the temporal resolution effect was determined by the slope function. Validation of the model was made to several locations of forests across the world. The results show that interception loss can be estimated by taking account the effects of depth of storage capacity into the model. The model can be applied to several locations in Malaysia and across the world. The finding of this study also may used to improve the understanding of forest interception model concepts.